An approximation to the Gini coefficient for a population based on sparse information for sub-groups - Michael Braulke (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1982)
Based on the assumption that the sectoral income distributions follow a Pareto distribution, a simple approximation to the aggregate Gini coefficient for a two-sector economy was developed which works on a minimum of information. As a matter of fact, merely the sectoral Gini coefficients, the mean incomes, and the distribution of population between sectors are needed to apply it. Its accuracy appears to be satisfactory and it should therefore be particularly useful, at least as a first investigative step, in the analysis of the income distribution of developing countries where the data base is small and the dual concept represents a meaningful approach, i.e. of countries with a distinctive difference between the export-sector, the modern sector or the urban sector etc. and the rest of the economy.
Keywords: 330